A definition and standardised terminology for Blue Intensity from Conifers - Björklund, Jesper; Seftigen, Kristina; Kaczka, Ryszard J.; Rydval, Miloš; Wilson, Rob (Dendrochronologia, 2024)
RW acknowledges funding from NSF/NERC project (NE/W007223/1) – Understanding Trans-Hemispheric Modes of Climate Variability: A Novel Tree-Ring Data Transect spanning the Himalaya to the Southern Ocean. KS and JB were supported by the Svenska Forskningsrådet Formas (grant no. 2019-01482) and the Stiftelsen Margit Althins stipendiefond (GS2021-0023). The published literature of the past 20 years expresses inconsistent terminology for the Blue Intensity (BI) method that could lead to confusion in analysis and interpretation. In this technical note we propose a standard terminology based around the prevalent use of BI for the variant that is positively correlated with wood density derived from X-ray and equivalent wood anatomical techniques. We highlight significant practical advantages of this standard terminology for data analysis, scientific interpretations as well as archiving, and provide some cautionary examples that could occur if not adhering to this terminology. In future studies using BI, we recommend to explicitly clarify that the standard terminology is used with the following phrase: The BI data produced in this study is consistent with the ‘2024 BI standard terminology’. Peer reviewed